Perancangan Sistem Informasi Klasifikasi Arsip BMKG Stasiun Meteorologi SMB II Kota Palembang - Aldo Iqbal Damoro; Muhamad Son Muarie (Universitas Katolik Widya Karya Malang, 2024)
Archives is a record of activities or a source of information in various forms created by institutions, organizations, or individuals in the context of their activities. Archives can take the form of letters, documents, deeds, charters, books, and others, which can serve as valid evidence for actions and decisions. With the advancement of technology, archives can also take the form of audio, video, and digital content. This research was conducted at one of the government institutions, namely the BMKG office in Palembang, SMB II Meteorology Station. The archiving procedure applied here is still done manually or semi-manually. The purpose of this research is to design an archive classification system at the BMKG office in Palembang, SMB II Meteorology Station, to assist in the development of the existing archiving system in the institution. The result of the research is an interface design that illustrates how the archive information system can be implemented in the institution. In this information system design, the author provides an overview and a simple display of the archive classification system, which is expected to help the institution manage its company archives